(untitled) (ENTHYMEMA, 2023)
Among the ‘authorizing’ processes of women playwrights and plays that are still considered ’minor’, translations and adaptations represent virtuous manipulations capable of undermining and renewing the system of values that establish the instances of canonicity. This article aims to explore some contemporary reverberations of Ana Caro’s comedy El conde Partinuplés (1653) and the first two prose interludes of the Tragicomedia de los jardines y campos sabeos (1624-1628) by Feliciana Enríquez de Guzmán. Specifically, the pages that follow will explore the ’double’ process of rewriting realized by translator and playwright Harley Erdman who, if on the one hand translated the aforementioned plays into English, including them in the volume Women Playwrights of Early Modern Spain (2016), on the other hand merged and adapted them in an original ‘refundición’ entitled Suitors (2013).